Tata Pamong Kolaboratif dalam Pengembangan Agrowisata “Kebun Desa” di Desa Tulungrejo, Kota Batu - Hamyana Hamyana; I Gede Nyoman Muditha; Muhammad Miftakhul Abidin (Institut Pertanian Bogor, 2022)
The development of the current development paradigm puts the government not only as a single actor but must be able to involve the community and other stakeholders. Collaborative governance can be used as one of the government's options in developing a model of government collaboration with stakeholders. However, the practice is not easy to apply, one of which is developing village garden agrotourism in Tulungrejo Village, Bumiaji District, Batu City. This study aims to identify factors that influence the collaborative governance model and measure the feasibility of the model in the development of Village Garden agrotourism. This research uses quantitative methods with a case study approach. The data were analyzed using a structural equation model (SEM) with the smart partial software tool least square-structural equation model (Smart PLS-SEM). The results showed that five factors affect collaborative governance, and it is known that commitment to process has the most significant real effect that is realized on the dependence between the factors involved and working together to achieve goals. As indicated by the normed fit index, the feasibility of the model is 48%, which is in the medium category. During the agrotourism research process, the Village Garden is still in the development stage and still requires further development. Keywords: Agrotourism, Collaborative governance, Kebun desa